Do higher education students have the means to learn during the Covid-19 pandemic? Student demands for distance learning in a suddenly digital landscape - Händel, Marion; Bedenlier, Svenja; Gläser-Zikuda, Michaela; Kammerl, Rudolf; Kopp, Bärbel; Ziegler, Albert (Journal for Educational Research Online, 2022)
Across the globe, 2020 terms began under conditions incited by the corona pandemic. Within a relatively short amount of time, universities started to develop and implement online courses for distance learning. These changes in learning and teaching may well have been a challenge for students.The current study is about an online survey at a German full-scale university investigating the unique circumstances under which students began the digital 2020 summer term. Of approximately 38,500 students, N = 5,563 students from across all institutional faculties took part in the survey. Results indicate how well students are equipped with devices for digital learning; what kind of experiences they have already made with online learning; and how competent they reported feeling regarding digital learning. Moreover, group differences between faculties, degrees, and gender were investigated. The study provides important insights into digital higher education during the exceptional pandemic situation. The results are intended to feed into student counselling systems via support by way of access to devices or courses regarding digital key competences, or through counselling for students with special social burden
Keywords: higher education; E-Learning; ICT skills; corona pandemic